Bodily Pain Intensity in Nursing Home Residents With Pressure Ulcers: Analysis of National Minimum Data Set 3.0. Issue 3 (7th April 2015) - Ahn, Hyochol; Stechmiller, Joyce; Fillingim, Roger; Lyon, Debra; Garvan, Cynthia
Abstract Clinical reports suggest that superficial pressure ulcers produce pain, but that pain decreases as the wound advances in stage. This study of the relationship between pressure ulcer stage and bodily pain intensity in nursing home residents was a secondary analysis of the national Minimum Data Set 3.0 assessment data in long‐term care facilities, collected from nursing home residents at least 65 years of age. Data were examined from residents with pressure ulcers who completed a bodily pain intensity interview between January and March 2012 (N = 41, 680) as part of the MDS comprehensive assessment. After adjusting for other variables (e.g., cognition, functional impairment, presence of comorbidities, use of scheduled pain medication, and sociodemographic variables), bodily pain intensity for those with more severe pressure ulcers in comparison to those with Stage I ulcers was higher by 11% (Stage II), 14% (Stage III), 24% (Stage IV), and 22% (suspected deep tissue injury). Because multivariate analysis showed that greater bodily pain intensity was associated with an advanced stage of pressure ulcer, health care providers should assess bodily pain intensity and order appropriate pain management for nursing home residents with pressure ulcers, particularly for those with advanced pressure ulcers who are vulnerable to greater bodily pain intensity. © 2015 Wiley Periodicals, Inc.